ANALISIS USAHA RANGKAIAN BUNGA (Studi Kasus Pada Florist Kalisari Semarang) - Niken Widyaningsih; Sri Marwanti; Shofia Nur Awami (Universitas Wahid Hasyim, 2014)
The purpose of research to find out how much it costs, net gains and factors affecting net income at Florist Kalisari Semarang. The sampling method used is a sampling technique (purposive sampling), the sample is 31 entrepreneurs flower arrangements. Methods of data collection using primary data and secondary data, while the method of data analysis using descriptive analysis and multiple regression. Total cost in this study is a fixed cost and variable cost. The average fixed cost Rp 5.701.172,00 and the average variable cost Rp 15.418.063,00. The average business revenue Rp 24.720.000,00 with the average amount of the total cost Rp 21.112.140,00 per month of February. The average net revenue earned Rp 3.607.860,00 at the “kios” with an average area of 32,20 m2. The use of production factors were obtained an average production of 124 units as flower arrangements. Regression analysis showed that all of the variables, the cost equipment depreciation and investment real positive effect on business net receipts flower arrangements while labor costs are significantly negative. Keywords: Agriculture, bussines analysis, florist business analysis